1951
DOI: 10.1085/jgp.34.4.451
|View full text |Cite
|
Sign up to set email alerts
|

The Desoxyribonucleic Acid Content of Animal Cells and Its Evolutionary Significance

Abstract: The DNA (desoxyribonucleic acid) content per cell, according to some recent investigations, is a constant for the various somatic cells of an organism, and sperm cells contain one-hail this amount per ceU (1, 2). The quantity of DNA per cell is a characteristic of each organism. In this work, done independentiy by two groups of investigators, the DNA per ceLl was found by determining the quantity of DNA in a suspension containing a known number of ceUs and then dividing the total DNA by the number of cells. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
1
1

Year Published

1954
1954
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 472 publications
(161 citation statements)
references
References 4 publications
5
149
1
1
Order By: Relevance
“…We suppose that the difference in chromatin structure which could be present in cells of different tissues of phylogenetically distant animals, such as fishes and mammals, can influence and even change the results of measurements and turn them to a nonproportional correlation of the DNA content. At least the dependence of the accessibility of different types of chromatin compaction to the dyes is well known (16,17,37,43). That is why the use of chicken or mammalian standards for measurements of the DNA content in cells of fishes (36,56,57) seems incorrect to us.…”
Section: Discussion a Problem Of The Internal Standardmentioning
confidence: 99%
“…We suppose that the difference in chromatin structure which could be present in cells of different tissues of phylogenetically distant animals, such as fishes and mammals, can influence and even change the results of measurements and turn them to a nonproportional correlation of the DNA content. At least the dependence of the accessibility of different types of chromatin compaction to the dyes is well known (16,17,37,43). That is why the use of chicken or mammalian standards for measurements of the DNA content in cells of fishes (36,56,57) seems incorrect to us.…”
Section: Discussion a Problem Of The Internal Standardmentioning
confidence: 99%
“…throughout the class of birds'' (Gulliver 1875, p. 475), and moreover that avian ''erythrocyte size appears to be related to the general metabolic activity of the species'' (Hartman and Lessler 1963, p. 467). For more than half a century it has been known that birds have genomes smaller than those of most other vertebrates Vendrely 1949, 1950;Mandel et al 1951;Mirsky and Ris 1951), and it was similarly shown very early that ''in the nucleated red cells of vertebrates . .…”
mentioning
confidence: 99%
“…It should be emphasized that explanations for the present cytophotometric observations can be advanced which do not necessarily contradict the generally accepted concept of DNA constancy (12,13). From each class of nuclei, 19 per cent of the DNA, a portion apparently not essential for cell life, has been dissociated from the chromatin under the influence of cortisone.…”
Section: Resultsmentioning
confidence: 47%